Interpretive Conventions - Mailloux, Steven (Cornell University Press, 2022)
In Interpretive Conventions, Steven Mailloux provides a general introduction to reader-response criticism while developing his own specific reader-oriented approach to literature. He examines five influential theories of the reading process—those of Stanley Fish, Jonathan Culler, Wolfgang Iser, Norman Holland, and David Bleich. He goes on to argue the need for a more comprehensive reader-response criticism based on a consistent social model of reading. He develops such a reading model and also discusses American textual editing and literary history.